Disclosure of operational performance in DSE listed companies. Do firm and industry characteristics matter? A balanced score card approach - Shaban Ngole; Ernest Mabonesho (Cogent Business & Management, 2023)
The purpose of this study is twofold: first, to examine the disclosure level of operational performance and second; to examine whether firm and industry characteristics matter in the disclosure of corporate information. The study uses data from twenty-one companies listed at the Dar Es Salaam Stock Exchange (DSE) for the financial year 2020/2021 and applies the Balanced Scorecard (BSC) framework. Data are collected from companies' websites by using content analysis approach. Moreover, the study uses disclosure index to determine the disclosure level of operational performance and presents the results using tables. The research reveals that there is high disclosure level of operational performance information at DSE. The study also finds that industry profile, listing-age and cross-listing matter on the disclosure of operational performance. The findings highlight that information related to customers and innovations are least disclosed this may be due to confidentiality and competitive advantage issues. Meanwhile, internal business process is highly disclosed in order to showcase strength to stakeholders. This study has used small sample size thus, future research may increase the sample size to include companies listed at other stock markets in order to increase diversity and get more insight on the operational performance and BSC framework in general. The findings are relevant to policy makers and regulatory bodies. The study contributes to the literature on the disclosure of operational performance information in an emerging capital market setting.
Keywords: M40; M41; 650; balanced Scorecard; disclosure; disclosure level; DSE; operational performance